Falls, sarcopenia, and growth in early life: findings from the Hertfordshire cohort study. - Sayer, A; Syddall, H; Martin, H; Dennison, E; Anderson, F; Cooper, C (2006)
Recent studies have shown that people whose early growth is poor have an increased risk of sarcopenia. Sarcopenia is an important risk factor for falls, but it is not known whether poor early growth is related to falls. The authors investigated this association in the Hertfordshire Cohort Study (1998-2004), where 2,148 participants from the United Kingdom provided their history of falls. Grip strength was used as a marker of sarcopenia. Birth weight, weight at 1 year, and conditional infant growth were analyzed in relation to history of falls. The prevalence of any fall in the last year was 14.3% for men and 22.5% for women. Falls in the last year were inversely related to adult grip strength, height, and walking speed in men and women as well as to lower conditional infant growth in men (odds ratio = 1.27, 95% confidence interval: 1.04, 1.56 per standard deviation decrease in conditional infant growth; p = 0.02). This association was attenuated after adjustment for grip strength. These findings support an association between poor early growth and falls in older men that appears to be mediated partly through sarcopenia. The lack of a relation with birth weight suggests that postnatal rather than prenatal influences on muscle growth and development may be important regarding the risk of falls in later life.